Cover Image. (19th April 2020) - Dittakavi, Sreekanth; Mahadevan, Lavanya; Chandrashekar, Devaraj V.; Bhamidipati, Ravi Kanth; Suresh, Juluri; Dhakshinamoorthy, Saravanakumar; Li, Ziyu; Baerenz, Felix; Tennagels, Norbert; Mullangi, Ramesh
Abstract : The cover image is based on the Short Communication High throughput screening assay for quantification of Cer d18:1/16:0, d18:1/24:0, d18:1/24:1, d18:1/18:0, d18:1/14:0, d18:1/20:0 and d18:1/22:0 ceramides in HepG-2 cells using RapidFire Mass spectrometry Ramesh Mullangi et al., https://doi.org/10.1002/bmc.4790.*** .